FAKTOR–FAKTOR YANG MEMPENGARUHI PENYERAPAN ANGGARAN DI SEKRETARIAT DPRD KABUPATEN MIMIKA - Sugeng Pristianto; Abu Bakar (ADMIN: Jurnal Administrasi Negara, 2023)
This research was compiled by the author to find out what factors influence the absorption of the budget at the Mimika Regency DPRD Secretariat. The number of respondents in this final assignment was 84 people with details of 57 Technical Implementation Officers for Activities, 21 Financial Management Officers/employees, 2 Budget Users. the variables in this final project consist of two variables, namely the independent variable and the dependent variable. The independent variables are Planning, Implementation of Procurement of Goods and Services, Administration, Human Resources and Goods and Services Providers while the dependent variable is the Absorption of the Budget at the Secretariat of the DPRD Kab. Mimika for the 2019 fiscal year to the 2022 fiscal year.